A functional variant of the serotonin transporter gene (SLC6A4) moderates impulsive choice in attention-deficit/hyperactivity disorder boys and siblings - Sonuga-Barke, Edmund; Kumsta, Robert; Schlotz, Wolff; Lasky-Su, Jessica; Marco, Rafaela; Miranda, Ana; Mulas, Fernando; Oades, Robert D.; Banaschewski, Tobias; Mueller, Ueli; Andreou, Penny; Christiansen, Hanna; et al. (Biological psychiatry, 2011)
Background - Impulsive drive for immediate reward (IDIR) and delay aversion are dissociable elements of the preference for immediate over delayed rewards seen in attention-deficit/hyperactivity disorder (ADHD). We hypothesized that IDIR would be associated with dopamine regulating genes and delay aversion would be associated with serotonin-regulating genes. - Methods - Impulsive drive for immediate reward and delay aversion were measured in 459 male children and adolescents (328 ADHD and 131 unaffected siblings) with a laboratory choice task. The sample was genotyped for the 5HTT (SLC6A4) promoter serotonin-transporter-linked polymorphic region polymorphism and a DAT1 (SLC6A3) 40-base pair variable number tandem repeat located in the 3′-untranslated region of the gene. - Results - There was no effect of dopamine transporter (DAT)1 on IDIR. As predicted, serotonin-transporter-linked polymorphic region s-allele carriers were more delay averse. This effect was driven by the s/l genotype in the ADHD group. These results were not altered by taking account of the rs25531 A/G single nucleotide polymorphism and were independent of age, IQ, and oppositional defiant disorder symptoms. - Conclusions - The results support the genetic distinctiveness of IDIR and delay aversion in ADHD and implicate serotonin function in delay aversion. Possible explanations of the heterosis effect in the ADHD cases are presented.